Comprehensive insights into the thermal and mechanical effects of metallic glasses via creep. (10th February 2022) - Xu, Z.R.; Qiao, J.C.; Wang, J.; Pineda, E.; Crespo, D.
Highlights: Evolution of deformation and relaxation behavior of a Zr-based MG was explored by extensive creep tests under physical aging and cyclic loading. Relaxation-time spectra were further utilized to quantitatively describe the time scales involve in the creep of MGs. An annihilation of local deformation units during physical aging and cyclic loading was detected through the diminution of amplitude in both activation energy and relaxation-time spectra. Abstract: Evolution of deformation and relaxation behaviors of a prototypical Cu46 Zr46 Al8 metallic glass was explored by extensive creep tests under both physical aging and cyclic loading. Deep insights into the microstructure-induced dynamic heterogeneity which accommodates creep deformation were successively revealed via experimental measurements and spectral analyses. An annihilation of local defects within metallic glass with increasing annealing time and cyclic numbers was observed through the reduction of amplitude in both activation energy spectra and relaxation-time spectra, which were also accompanied by an ascending value of β K W W . It is further found that the corresponding deformation units within the metallic glass do not disappear permanently, but are recoverable over the course of cyclic loading. The apparent suppressed relaxation process can be gradually alleviated with increasing resuming time between two consecutive cycles, behaving differently from physical aging, which indicates a notable discrepancy between thermal treatment and mechanical treatment. Graphical abstract: Image, graphical abstract